Portraits of Home: Working in Community Daycare Homes in New Brunswick (LEARNing Landscapes, 2013)
Part of a larger project involving the design and implementation of a first-time curriculum framework for early childhood care and learning in New Brunswick, this paper highlights the stories of Canadian early childhood educators working in home-based daycares. In particular, a common theme of "sense of place" is discussed in relation to four portraits that are presented in this article: (1) Home as Survival, (2) Transition to Home, (3) Home as Transition, and (4) Coming Home. Through each portrait, the role of life changes and transitioning towards new beginnings is discussed, along with possibilities and constraints for ongoing discussion and reflection.
Keywords: early childhood; care; home-based daycare; curriculum; sense of place; home